Answer:
1) The factors of
are
![\mathbf{(x-1)(x-2)=0}](https://img.qammunity.org/2021/formulas/mathematics/college/mbvddqo6y1oj6lu0dda754e83n5kjcid6w.png)
Option C is correct.
3) The factors of
are
![\mathbf{(x-2)(x+4)=0}](https://img.qammunity.org/2021/formulas/mathematics/college/x8pdvr4ptin9uif4ds97ltx40ud5all7d2.png)
Option B is correct.
Explanation:
1) Factor :
![x^2-3x+2=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/dw1muqpmdsa0cy2abg7ah2diprvrilxu7h.png)
For factoring we need to break the middle term, such that there sum is equal to middle term of expression and product is equal to product of first and last term.
The middle term : -3x
We can break them as (-2x)( -x)
Solving:
![x^2-3x+2=0\\x^2-2x-x+2=0\\x(x-2)-1(x-2)=0\\(x-1)(x-2)=0](https://img.qammunity.org/2021/formulas/mathematics/college/flng15o4q23rzs3brx1que7t6zu98j820x.png)
So, factors of
are
![\mathbf{(x-1)(x-2)=0}](https://img.qammunity.org/2021/formulas/mathematics/college/mbvddqo6y1oj6lu0dda754e83n5kjcid6w.png)
Option C is correct.
3) Factor:
![x^2+2x-8=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/enyd0y2xduiz733nuv5wpa5r39lmfztod2.png)
For factoring we need to break the middle term, such that there sum is equal to middle term of expression and product is equal to product of first and last term.
The middle term : 2x
We can break them as (4x)( -2x)
Solving
![x^2+2x-8=0\\x^2+4x-2x-8=0\\x(x+4)-2(x+4)=0\\(x-2)(x+4)=0](https://img.qammunity.org/2021/formulas/mathematics/college/v22f9jciuzud5uovfyes5o67gi4zx1mvhy.png)
So, factors of
are
![\mathbf{(x-2)(x+4)=0}](https://img.qammunity.org/2021/formulas/mathematics/college/x8pdvr4ptin9uif4ds97ltx40ud5all7d2.png)
Option B is correct.